Application of a Simple Parkinson's Disease Risk Score in a Longitudinal Population‐Based Cohort. Issue 9 (3rd June 2020) - Marini, Kathrin; Mahlknecht, Philipp; Tutzer, Franziska; Stockner, Heike; Gasperi, Arno; Djamshidian, Atbin; Willeit, Peter; Kiechl, Stefan; Willeit, Johann; Rungger, Gregorio; Noyce, Alastair J.; Schrag, Anette; et al.
Abstract: Background: Identifying individuals at risk of developing Parkinson's disease (PD) is critical to define target populations for future neuroprotective trials. Objective: The objective of this study was to apply the PREDICT‐PD algorithm of risk indicators for PD in a prospective community‐based study (the Bruneck study), representative of the general elderly population. Methods: PREDICT‐PD risk scores were calculated based on risk factor assessments obtained at baseline (2005, n = 574 participants). Cases of incident PD were identified at 5‐year and 10‐year follow‐ups. Participants with PD or secondary parkinsonism at baseline were excluded (n = 35). We analyzed the association of log‐transformed risk scores with the presence of well‐established markers as surrogates for PD risk at baseline and with incident PD at follow‐up. Results: A total of 20 participants with incident PD were identified during follow‐up (11 after 5 years and 9 after 10 years). Baseline PREDICT‐PD risk scores were associated with incident PD with odds ratios of 2.09 (95% confidence interval, 1.35–3.25; P = 0.001) after 5 years and of 1.95 (1.36–2.79; P < 0.001) after 10 years of follow‐up per doubling of risk scores. In addition, higher PREDICT‐PD scores were significantly correlated with established PD risk markers (olfactory dysfunction, signs of rapid eye movement sleep behavior disorder and motor deficits) and significantly associated with higher probability for prodromal PD according to the Movement Disorder Society research criteria at baseline. Conclusions: The PREDICT‐PD score was associated with an increased risk for incident PD in our sample and may represent a useful first screening step in future algorithms aiming to identify cases of prodromal PD. © 2020 The Authors. Movement Disorders published by Wiley Periodicals, Inc. on behalf of International Parkinson and Movement Disorder Society.